2020
DOI: 10.1371/journal.pone.0228993
|View full text |Cite
|
Sign up to set email alerts
|

Deep-rooted pigeon pea promotes the water relations and survival of shallow-rooted finger millet during drought—Despite strong competitive interactions at ambient water availability

Abstract: Bioirrigation has been defined as the transfer of hydraulically lifted water by a deep-rooted plant to a neighbouring shallow-rooted plant which cannot access deep soil moisture. In this study, we tested if facilitative effects of bioirrigation or the competition for water dominate the interaction of two intercropped plants-deep-rooted pigeon pea (PP) and shallow-rooted finger millet (FM) before and during a drought. Additionally, we tested how the presence of a common mycorrhizal network (CMN) affects the bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 48 publications
2
22
1
Order By: Relevance
“…Bio-irrigation is another beneficial phenomenon by which shallow-rooted crops obtain support from deep-rooted ones in intercropping under limited moisture conditions. The experimental results clearly indicated that deep-rooted pigeon pea played the role of bio-irrigators and shared moisture for shallow-rooted finger millet [67,68].…”
Section: Water Managementmentioning
confidence: 88%
See 1 more Smart Citation
“…Bio-irrigation is another beneficial phenomenon by which shallow-rooted crops obtain support from deep-rooted ones in intercropping under limited moisture conditions. The experimental results clearly indicated that deep-rooted pigeon pea played the role of bio-irrigators and shared moisture for shallow-rooted finger millet [67,68].…”
Section: Water Managementmentioning
confidence: 88%
“…The transported water to the upper layer of the soil is utilized by lateral secondary branches of the roots of the same crop and neighbouring crops also share it. The experimental results clearly indicated that deep-rooted pigeon pea shared played the role of bio-irrigators and shared moisture for shallowrooted finger millet [67,68]. Moreover, Chai et al [142] mentioned that WUE was increased by 95% in a maize + pea intercropping system over the pure stand of pea.…”
Section: Available Soil Moisturementioning
confidence: 93%
“…Annual global estimates of N fixed by legumes in symbiosis with soil rhizobia were reported to be 21.5 Tg (Herridge et al 2008) of which up to 30% is estimated to be returned to soils (Reeves et al 2016). Other reported benefits of including legumes into crop rotations are greater microbial and crop diversity, soil fertility, and reduction of pest incidence (Diatta et al 2016a;Franke et al 2018;Giller 2001;Matusso et al 2014;Singh et al 2020;Vanlauwe et al 2019). In addition, legume crops are an important and economic source of protein, minerals, and vitamins in human diets and animal feed under smallholder agriculture (Diatta et al 2016b;Graham and Vance 2003;Tharanathan and Mahadevamma 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent work has shown that a CMN plays a key role in facilitating the transfer of water between the rhizospheres of two intercropped partners in a greenhouse and can in turn improve the water relations of shallow rooted crops during soil drying (Singh et al ., 2019). However, a further experiment with bigger pots (50 L) than in the previous experiment did not show an effect of the CMN on water-relations but treatments with CMN had lower foliar damage than treatments without CMN during drought (Singh et al ., 2020).…”
Section: Introductionmentioning
confidence: 87%